Transcriptomic and proteomic analysis of iris tissue and aqueous humor in juvenile idiopathic arthritis-associated uveitis. (June 2019) - Wildschütz, Lena; Ackermann, Doreen; Witten, Anika; Kasper, Maren; Busch, Martin; Glander, Shirin; Melkonyan, Harutyun; Walscheid, Karoline; Tappeiner, Christoph; Thanos, Solon; Barysenka, Andrei; Koch, Jörg; et al.
Abstract: Gene and protein expression profiles of iris biopsies, aqueous humor (AqH), and sera in patients with juvenile idiopathic arthritis-associated uveitis (JIAU) in comparison to control patients with primary open-angle glaucoma (POAG) and HLA-B27-positive acute anterior uveitis (AAU) were investigated. Via RNA Sequencing (RNA-Seq) and mass spectrometry-based protein expression analyses 136 genes and 56 proteins could be identified as being significantly differentially expressed (DE) between the JIAU and POAG group. Gene expression of different immunoglobulin (Ig) components as well as of the B cell-associated factors ID3, ID1, and EBF1 was significantly upregulated in the JIAU group as compared to POAG patients. qRT-PCR analysis showed a significantly higher gene expression of the B cell-related genes CD19, CD20, CD27, CD138, and MZB1 in the JIAU group. At the protein level, a significantly higher expression of Ig components in JIAU than in POAG was confirmed. The B cell-associated protein MZB1 showed a higher expression in JIAU patients than in POAG which was confirmed by western blot analysis. Using bead-based immunoassay analysis we were able to detect a significantly higher concentration of the B cell-activating and survival factors BAFF, APRIL, and IL-6 in the AqH of JIAU and AAU patients than in POAG patients. The intraocularly upregulated B cell-specific genes and proteins in iris tissue suggest that B cells participate in the immunopathology of JIAU. The intracameral environment in JIAU may facilitate local effector and survival functions of B cells, leading to disease course typical for anterior uveitis. Highlights: Iris of juvenile idiopathic arthritis-associated uveitis (JIAU) is characterized by distinct gene and protein expression. Gene and proteome expression point to presence and longevity of B cells and plasma cells in the iris of JIAU patients. Elevated BAFF and APRIL concentrations in aqueous humor of JIA-uveitis may contribute to longevity of B and plasma cells.